ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK KELAS IV DI SDN 5 DAWUHAN KABUPATEN SITUBONDO TAHUN PELAJARAN 2016/2017 - Andi Lukman Faizal; Mory Victor Febrianto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
This study entitled "Analysis of Student Learning Difficulties in Learning Thematic Class IV at SDN 5 Dawuhan Situbondo in the academic year 2016/2017".The background of this study is the fourth grade students of SDN 5 Dawuhan have difficulty learning in thematic learning. These problems make researchers interested in conducting further research. The purpose of this study was to determine students' learning difficulties in thematic learning class IV SDN 5 Dawuhan.This research is a qualitative descriptive study or research. Data obtained from this study by using observation, interview teachers and students, as well as documentation. The results of this study revealed students' learning difficulties in thematic learning. Learning difficulties of various factors. Among them, the internal factors and external factors. Internal factors students are students 'attitudes toward learning, students learn concentration, self-confidence of students, students' intellectual, and the nature of the student who likes to joke. While external factors of learning difficulties is the lack of motivation to learn, learning support factors, the school environment, and friend groups